2020
DOI: 10.3390/cancers12061485
|View full text |Cite
|
Sign up to set email alerts
|

T1 Glottic Cancer: Does Anterior Commissure Involvement Worsen Prognosis?

Abstract: Radiotherapy (RT) and transoral laser microsurgery (TLM) represent the main treatment modalities for early glottic carcinoma. Local failure is notoriously more frequent in T1b glottic cancer in comparison to T1a and T2 tumors. In this scenario, the role of anterior commissure (AC) involvement is still controversial. The aim of the present study was therefore to determine its potential prognostic power in worsening patients’ survival and outcomes. We categorized different tumor glottic fold locations with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…Tumor involvement of the AC has been cited as a potential prognostic factor for T1 glottic carcinoma, but no staging system has adopted it within their guidelines 8 . Previous authors have recognized the importance of adjusting guidelines to take into account AC involvement for staging T1 glottic cancers 2,9,20 . Despite the lack of recognition as an independent risk factor within the current AJCC guidelines, involvement of the AC drastically increases the risk of recurrence in both T1a and T1b glottic cancers 2,9,18,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor involvement of the AC has been cited as a potential prognostic factor for T1 glottic carcinoma, but no staging system has adopted it within their guidelines 8 . Previous authors have recognized the importance of adjusting guidelines to take into account AC involvement for staging T1 glottic cancers 2,9,20 . Despite the lack of recognition as an independent risk factor within the current AJCC guidelines, involvement of the AC drastically increases the risk of recurrence in both T1a and T1b glottic cancers 2,9,18,22 .…”
Section: Discussionmentioning
confidence: 99%
“…The Surveillance, Epidemiology, and End Results (SEER) program is an online database through the National Cancer Institute (NCI) and National Institutes of Health (NIH) that publishes cancer statistics in the United States. All previous studies comparing outcomes between T1a and T1b glottic cancers have been single‐institution retrospective studies with limited sample sizes 2,8,9 . For this study, we used the SEER database to compare Stage I T1a and T1b glottic cancers to evaluate differences in treatment and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available literature has demonstrated that the malignant tumors of the anterior commissure have a worse prognosis [24]. In these cases, the senior author's attitude is to perform a wide, subpericondrial excision and classify the procedure as a type VI cordectomy.…”
Section: Anterior Commissurementioning
confidence: 99%
“…Baseline Characteristics of Old Patients (≥ 65 Years) different result may be attributed to the fact that Rutkowski et al enrolled only patients with T2 cancer.It is important to mention that patients afflicted with early glottic cancer are not a single entity, but a quite heterogeneous group with great complexity and possibility,32 and thus the treatment selection between open surgery and endoscopic approach of this population is intricate. Meticulous selection of the ideal patients who can benefit the most from ELS, and offering rigorous follow-up procedures to detect recurrence in time are recommended.…”
mentioning
confidence: 99%